The Dynamics of Muhammadiyah Islamic Education (1912-2019) - Sudarmin, Sudarmin; Ansori, M Afif; Andari, An An; Fuadah, Anis; Nisa, Khairun (Yupa: Historical Studies Journal, 2024)
This research aims to understand the changes within Muhammadiyah's Islamic educational institutions, including the influencing factors and the programs developed to enhance the quality and effectiveness of the education provided. This research identifies factors influencing the development of these educational institutions, including political policies, socio-cultural changes, technological advancements, and Muhammadiyah's educational thoughts and movements. The findings reveal four dynamic periods of educational development within the Muhammadiyah organization: the pioneer period (1900-1923), the development period (1923-1970), the institutionalization period (1970-1998), and the transformation period (1998-present). In the 1970s, the development of Islamic education within Muhammadiyah began with religious-plus schools, which later formed the basis for establishing Muhammadiyah boarding schools.